Parasitic myoma after transabdominal hysterectomy for fibroids: a case report - Jiao Wang; Guipeng Liu; Qing Yang (BMC, 2023)
Abstract Background Parasitic myomas typically occur after a pedunculated subserosal fibroid loses its uterine blood supply and parasitizes other organs or after a surgery involving morcellation techniques. Parasitic myomas that occur after transabdominal surgery are extremely rare and may not be sufficiently documented. Here, we present a case of parasitic myoma in the anterior abdominal wall following a transabdominal hysterectomy for fibroids. Case presentation The patient was a 46-year-old Chinese woman who had undergone surgery for uterine myomas at our hospital 1 year prior. The patient later revisited our department with a palpable mass in her abdomen, and imaging revealed a mass in the iliac fossa. The possibility of a broad ligament myoma or solid ovarian tumor was considered before surgery, and laparoscopic exploration was performed under general anesthesia. A tumor measuring approximately 4.5 × 4.0 cm was found in the right anterior abdominal wall, and a parasitic myoma was considered. The tumor was completely resected. Pathological analysis of the surgical specimens suggested leiomyoma. The patient recovered well and was discharged on postoperative day 3. Conclusion This case suggests that parasitic myoma should be considered in the differential diagnosis of patients presenting with abdominal or pelvic solid tumors with a history of surgery for uterine leiomyomas, even without a history of laparoscopic surgery using a power morcellator. Thorough inspection and washing of the abdominopelvic cavity at the end of surgery is vital.